The Utilization of Android-Based Learning Media at Madrasah Ibtidaiyah (MI) Bahrul Ulum Jombang - Machnunah Ani Zulfah; Soffy Mauladani (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The use of an android handphone in MI Bahrul Ulum Tambakberas Jombang aims to support the learning of Islamic education and find out what are the obstacles and how to overcome these obstacles in order to achieve maximum learning achievement. The formulation of this study: First, how is the use of Android mobile phones as a support for learning fiqih education for students of MI Bahrul Ulum Tambakberas Jombang? Secondly, what are the factors of constraints in the utilization of an Android handphone as a support for learning fiqih education for students of MI Bahrul Ulum Tambakberas Jombang? This study aims to obtain answers to the utilization of Android mobile phones in the MI Bahrul Ulum Tambakberas Jombang North Vocational High School and the inhibiting factors and how to overcome the inhibiting factors in utilizing the Android handphone itself. The qualitative approach used is descriptive and interactive method with observation, documentation, and interview techniques. The results of this study indicate that before the implementation of the Android mobile phone utilization program the condition of student learning achievement was far from expected. After the application of the program on the use of Android phones proved to be a different result, the students were easier to access school assignments because in the Android mobile the students could easily access anything through the internet and the students' learning achievement increased. The inhibiting factor is the difficulty of the internet network during bad weather.